Demographics and complaints of university students who sought help at a campus mental health service between 1987 and 2004 - Oliveira, Maria Lilian Coelho de; Dantas, Clarissa de Rosalmeida; Azevedo, Renata Cruz Soares de; Banzato, Cláudio Eduardo Muller (São Paulo Medical Journal, 2008)
context and Objective: Client characterization is an important step in evaluating the services offered by campus counseling and mental health centers and in their further planning and development. The objectives here were to describe reported complaints and demographics among students who sought counseling/mental healthcare at a Brazilian campus mental health service over a 17-year period and to compare these characteristics with those of the general university student body. DESIGN AND SETTING: Retrospective study at the Psychological and Psychiatric Service for Students (SAPPE), Universidade Estadual de Campinas (Unicamp). Methods: The participants were all of the 2,194 students who sought counseling/mental health care at SAPPE from 1987 to 2004. Information was obtained from clients’ clinical charts. Unicamp’s database was consulted for general information on its students. Results: The findings indicated overrepresentation, among the clients, of undergraduates, female students, students from Brazilian states other than São Paulo, students living in the campus residence hall and those whose main source of income was a scholarship grant. We also found overrepresentation of Humanities and Arts students among the clients. The most frequently reported complaints were difficulties in interpersonal relationships, family conflicts and poor academic performance. Conclusion: Course level (undergraduate or postgraduate), study field, living in a university residential facility and reliance on a scholarship grant were found to influence the behavior of seeking mental health counseling among Brazilian university students in this study. Course level was found to influence the pattern of complaints reported at first contact with the mental health service.